European women in neurosurgery: I – A chronology of trailblazers. (April 2021) - Hernández-Durán, Silvia; Murphy, Mary; Kim, Eliana; Al-Shehhi, Noora; Broekman, Marike; de Praeter, Mania; Dubuisson, Annie; Emery, Évelyne; Gazioglu, Nurperi; Grossman, Rachel; Janssen, Insa Katrin; Karampouga, Maria; et al.
Highlights: European women were present from the dawn of the specialty in 1920′s. Women in European neurosurgery have been pioneers and conquered great adversity. Throughout the decades, female participation in European neurosurgery has increased. Currently, the proportion of women in European neurosurgery has increased. Abstract: Neurosurgery as a distinct speciality has been around for 100 years. Some of the earliest women neurosurgeons were European, emerging from the 1920′s onwards. Here we detail the rise of women in neurosurgery across Europe with a decade by decade account of big events and firsts across the continent. The emerging themes are seen in stories of pioneers with enormous resilience, camaraderie, trailblazing and triumphing in a system with great obstacles and challenges. Our journey through this chronology brings us to the modern day, where most European countries have or have had a woman neurosurgeon and the future for women in neurosurgery in the continent is very bright.